A behavioral test battery only reveals Sex-Specific Differences in Spatial Reference Memory Acquisition in C57BL/6JRj Mice - Melgar-Locatelli, Sonia; Mañas-Padilla, María del Carmen; Gavito, Ana Luisa; Rivera-González, Patricia; Rodríguez-Pérez, Celia; Castilla-Ortega, María Estela; Castro-Zavala, Adriana (My University, 2024)
Sex disparities in declarative and spatial memory exist in humans, favoring either gender depending on the task. This trend is observed in rats but less so in mice. In our study with C57BL/6JRj mice, we conducted various tests and found no gender differences in locomotion, emotions, or object recognition. However, in the water maze task, males learned faster but both genders reached similar long-term memory levels. Hippocampal brain-derived neurotrophic factor (BDNF) expression showed no significant gender variability in free-cycling female mice. This emphasizes the need to consider sex-based differences in animal models and include female mice in behavioral research.
Keywords: Memoria - Diferencias sexuales; Morris water maze; Object recognition; Females Variability; BDNF